(untitled) - Polohova, Marta (Aura musica, 2013)
The content of this paper is focusing on Slovak national music composer person Mikulas Moyzes. The author maps the journey of his life and benefits of his musical activities, and educational outreach activities. In the next part of this paper briefly describes his compositional output by specifying anthology called: Thirty Slovak folk songs for a female trio. Notes to the text in it, songwriting approach and interpretative aspects.
Keywords: Mikulas Moyzes; Austria-Hungary; slovak national music; girls' teachers college; artificial songs; choral music; adaptations of folk songs